IMPROVING THE COORDINATIVE CAPABILITIES THROUGH BADMINTON GAME FOR CHILDREN OF 4TH GRADE - Andreea - Gabriela Lazăr (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The aim of the research was to track the effects of badminton play, on the coordination capabilities and on some forms of manifestation of speed motor quality. The experiment took place in the gymnasium of the "Ştefan cel Mare" General School in Putna, on a group of 17 students from the 4th grade. They formed the experimental group. The control group consisted of 14 pupils of the fourth grade at Gura Putnei General School. The independent variable consisted in applying badmintonspecific means to the experimental group. After applying the badminton means, there was a faster progression of the coordination and velocity indexes in the experimental group compared to the control group qualities. Badminton game, a new, beautiful and dynamic game for students, has influenced the level of coordination and speed, but has also made impact on the more active and enjoyable involvement of children in Physical Education and Sports lessons. Teaching badminton at any age complements children's motorcycle baggage in a surprising way.